1998
DOI: 10.1099/00221287-144-8-2025
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of streptococcal plasmin receptor protein (Plr) identifies the C-terminal Lys334 as essential for plasmin binding, but mutation of the plr gene does not reduce plasmin binding to group A streptococci

Abstract: Plasmin(ogen) binding is a common property of many pathogenic bacteria including group A streptococci. Previous analysis of a putative plasmin receptor protein, Plr, from the group A streptococcal strain 64/14 revealed that it is a glyceraldehyde-3-phosphate dehydrogenase and that the plr gene is present on the chromosome as a single copy. This study continues the functional characterization of Plr as a plasmin receptor. Attempts at insertional inactivation of the plr gene suggested that this single-copy gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…Previous studies have shown that group A streptococci bind plasminogen by four surface receptors: group A streptococcal M-like protein, enolase, GAPDH and most recently PAM-related protein Prp (Pancholi & Fischetti, 1998;Winram & Lottenberg, 1998;Walker et al, 2005;Sanderson-Smith et al, 2007). Enolase and GAPDH are known to contain lysine residues (Derbise et al, 2004) and are, therefore, efficient binders of plasminogen.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that group A streptococci bind plasminogen by four surface receptors: group A streptococcal M-like protein, enolase, GAPDH and most recently PAM-related protein Prp (Pancholi & Fischetti, 1998;Winram & Lottenberg, 1998;Walker et al, 2005;Sanderson-Smith et al, 2007). Enolase and GAPDH are known to contain lysine residues (Derbise et al, 2004) and are, therefore, efficient binders of plasminogen.…”
Section: Discussionmentioning
confidence: 99%
“…Examples are the glyceraldehyde-3-phosphate dehydrogenase of group A streptococci (25) and the cell surface lipoprotein of B. burgdorferi (3). Moreover, site-directed mutagenesis of the streptococus plasminogen receptor confirmed that C-terminal lysyl residues are required for binding (26). In this regard it is worth pointing out that the M. tuberculosis genome database (2) documents the existence of an ␣-enolase (Rv1023) and a glyceraldehyde-3-phosphate dehydrogenase (Rv2982c) with Cterminal lysyl residues.…”
mentioning
confidence: 99%
“…In GAS, glucose is metabolized solely by the glycolytic pathway, as GAS lacks the tricarbolicacetic acid (TCA)-metabolic cycle and the Entner-Doudoroff alternative metabolic pathway (1,2,13,29,43). The multifunctional SDH is encoded by a single essential gene (33,45). The gene knockout approach to prevent SDH expression in GAS, therefore, is not feasible.…”
mentioning
confidence: 99%
“…The gene knockout approach to prevent SDH expression in GAS, therefore, is not feasible. The site-directed mutagenesis strategies that allow alteration in the specific functional domains without disturbing the conformational structure responsible for the catalytic function have been successfully employed to create Plg-binding enolase-and SDH/Plr-specific deletion mutants (3,12,45). Since the putative transport system responsible for exporting the anchorless metabolic surface enzymes is not known, it has not been possible to create a GAS mutant in which the anchorless enzyme is selectively retained in the cytoplasm and not expressed on the surface.…”
mentioning
confidence: 99%